Paleoceanography and ice sheet variability offshore Wilkes Land, Antarctica - Part 1: Insights from late Oligocene astronomically paced contourite sedimentation - Salabarnada, Ariadna; Escutia, Carlota; Röhl, Ursula; Nelson, C. Hans; McKay, Robert M.; Jiménez Espejo, Francisco J.; Bijl, Peter K.; Hartman, Julian D.; Strother, Stephanie L.; Salzmann, Ulrich; Evangelinos, Dimitris; López-Quirós, Adrián; et al. (Climate of the Past, 2018)
Antarctic ice sheet and Southern Ocean paleoceanographic configurations during the late Oligocene are not well resolved. They are however important to understand the influence of high-latitude Southern Hemisphere feedbacks on global climate under CO scenarios (between 400 and 750 ppm) projected by the IPCC for this century, assuming unabated CO emissions. Sediments recovered by the Integrated Ocean Drilling Program (IODP) at Site U1356, offshore of the Wilkes Land margin in East Antarctica, provide an opportunity to study ice sheet and paleoceanographic configurations during the late Oligocene (26-25 Ma). Our study, based on a combination of sediment facies analysis, magnetic susceptibility, density, and X-ray fluorescence geochemical data, shows that glacial and interglacial sediments are continuously reworked by bottom currents, with maximum velocities occurring during the interglacial periods. Glacial sediments record poorly ventilated, low-oxygenation bottom water conditions, interpreted as resulting from a northward shift of westerly winds and surface oceanic fronts. Interglacial sediments record more oxygenated and ventilated bottom water conditions and strong current velocities, which suggests enhanced mixing of the water masses as a result of a southward shift of the polar front. Intervals with preserved carbonated nannofossils within some of the interglacial facies are interpreted as forming under warmer paleoclimatic conditions when less corrosive warmer northern component water (e.g., North Atlantic sourced deep water) had a greater influence on the site. Spectral analysis on the late Oligocene sediment interval shows that the glacial-interglacial cyclicity and related displacements of the Southern Ocean frontal systems between 26 and 25Ma were forced mainly by obliquity. The paucity of iceberg-rafted debris (IRD) throughout the studied interval contrasts with earlier Oligocene and post-Miocene Climate Optimum sections from Site U1356 and with late Oligocene strata from the Ross Sea, which contain IRD ...